Physical Activity Level Among Military Veterans in Marang, Terengganu, Malaysia - Sedek, Razalee; Kasim, Nurul Ilma; Ahmad, Nazirah (Pakistan Journal of Nutrition, 2020)
Background and Objective: The increase in obesity among male military veterans (MVs) is often associated with low levels of physical activity and unhealthy food intake. This situation causes various health diseases if actions are not undertaken to overcome this problem. Therefore, this study aimed to evaluate the level of physical activity and to determine the relationship between body mass index (BMI) and physical activity level among MVs in Marang, Terengganu, Malaysia. Materials and Methods: This study involved 209 male MVs aged 40-60 years old. Data collection involved anthropometric measurements, including weight, height and waist circumference (WC). Meanwhile, the instrument comprised questions regarding sociodemographic characteristics, health status and physical activity habits. The physical activity level (PAL) was measured using the International Physical Activity Questionnaire (IPAQ). Results: This study showed that 41.1% of the respondents were categorized as normal weight, 42.1% overweight and 16.8% obese. The mean weight, height, BMI and waist circumference were 75.213.5 kg, 169.76.3 cm, 26.14.2 kg m–2 and 83.99.7 cm, respectively. A total of 20% of respondents showed a WC of more than 90 cm and were considered to be at high risk of cardiovascular disease and diabetes. Most of the subjects preferred sedentary behaviour, such as watching television/listening to the radio (52.6%), to exercise (7.2%). The average PAL of the respondents was 2445.8±642.1, with most of the respondents reporting a moderate PAL (81.3%) compared to a high (15.8%) or low PAL (2.9%). There was a negative correlation (p<0.01) between BMI and low, medium and high MET physical activity scores r = 0.210, p = 0.002; r = 0.638, p<0.001; r = 0.423, p<0.001, respectively). Conclusion: Most of the MVs in this study had moderate PALs. The Veterans Association of Malaysia Armed Forces can use the information collected to plan health-related programmes to prevent unhealthy lifestyles and chronic diseases among MVs.